Diabetes Insulin Guidance System: a real‐world evaluation of new technology (d‐Nav) to achieve glycaemic control in insulin‐treated type 2 diabetes. (September 2015) - Donnelly, R; Carr, S; Harper, R
Abstract The aim was to conduct a service evaluation of the effectiveness of using d‐Nav (a handheld device that automates the process of insulin dosage titration using the Diabetes Insulin Guidance System [DIGS] software) in achieving glycaemic control in patients with type 2 diabetes. The study comprised an exploratory single‐centre pilot evaluation of the use of d‐Nav in patients with type 2 diabetes aged ≥21 years with an HbA1c level ≥53 mmol/mol (≥7.0%) who were receiving insulin therapy for at least one year. Patients were asked to use d‐Nav to monitor their blood glucose level before every insulin injection and, when they suspected the occurrence of hypoglycaemia, to allow d‐Nav to adjust their insulin dosage. At scheduled three‐monthly clinic visits, HbA1c was measured and information on episodes of hypoglycaemia collected from d‐Nav and by patient reporting. Patients were followed for a minimum of six months. A total of 94 patients completed the evaluation as active users. The mean (± standard deviation) HbA1c for active users decreased from 77 ± 15 mmol/mol (9.2 ± 1.4%) at baseline to 62 ± 13 mmol/mol (7.8 ± 1.2%) at the three‐ to five‐month clinic visit and to 59 ± 13 mmol/mol (7.5 ± 1.2%) at the six‐ to 12‐month clinic visit. In patients for whom paired data were available, the decreases were statistically significant at both post‐baseline visits (both p < 0.001). The frequency of minor hypoglycaemia (blood glucose ≤3.6 mmol/L) was low and well within the tolerated range. In conclusion, d‐Nav is shown to be a safe and effective solution for blood glucose management in insulin users with type 2 diabetes. Copyright © 2015 John Wiley & Sons.